Development of Blender-Based Animation Video Tutorial Learning Media on Body SPA Material - Maya Sari, Dian; Bornlida Br Ginting, Fourteen; Rambe, Armaini (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The low interest in learning and understanding of students in studying Body Spa material is caused by the limitations of the learning media used by teachers, as well as the lack of interesting and interactive media. The purpose of this study is to develop learning media in the form of animated video tutorials based on Blender on Body SPA material for class XI students of SMK Swasta Imelda. This study is an R&D study with the ADDIE model, which includes five stages, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The research instrument used was a questionnaire with a data analysis technique, namely descriptive statistics. The validation results from media experts and material experts showed that the learning media developed was very feasible to use, with an assessment of material experts with an average feasibility of 89% and media experts with an average of 88% with a very feasible category. The results of the small group trial were 87%, the medium group trial was 88.33% and the large group trial was 90% with the category Very Feasible. These results indicate that students gave a positive response to this animated video. This media is considered interesting, easy to understand, and able to increase students' motivation and understanding of Body Spa material. The use of animated video tutorial learning media based on Blender can increase students' learning motivation, especially in beauty expertise competencies.